Model Latihan Teknik Tendangan Ijeung pada Atlet Taekwondo Universitas Negeri Jakarta - Teddy Fadilla Aqman; Fahmy Fachrezzy; Mansur Jauhari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to develop an Ijeung Kick Technique Training Model for Taekwondo Athletes at Jakarta State University. In accordance with the objectives used by researchers, namely up to five research steps or up to the expert validation stage where this research uses the ADDIE research and development (R&D) research method. To get the right model according to the aim of developing a training model based on the theory of basic Ijeung kick techniques in the taekwondo sport being studied. After researching, the researchers created a book on the Ijeung Kick Technique Training Model for Taekwondo Athletes at Jakarta State University. The next stage was the validation process carried out by three taekwondo expert studies (expert judgment). In the book Ijeung Kick Technique Training Models for Jakarta State University Taekwondo Athletes, researchers explain, design, seventeen training models developed from the Ijeung taekwondo kick technique, in order to provide benefits for Jakarta State University athletes and improve students' skills and abilities in performing kick techniques as well as opening Athletes believe that good and correct skills are very important, especially in the Ijeung kick because it is an important mental kick and can produce points. The conclusion of the book is the Ijeung Kick Technique Training Model for Taekwondo Athletes at Jakarta State University, that the Ijeung kick technique training model for Jakarta State University athletes is suitable for use in taekwondo training.